Expanding the Reach of Education Reforms Perspectives from Leaders in the Scale-Up of Educational Interventions - Glennan, Jr (RAND Corporation, 2004)
How does one spread a successful educational reform? The essays here recount the authors' experiences with the scale-up process. Among their lessons are the importance of building the capacity to implement and sustain the reforms, adjusting for local culture and policy, ensuring quality control, providing the necessary infrastructure, and fostering a sense of ownership. The process is iterative and complex and requires cooperation among many actors who must ensure that the results align with goals.